Experimental overview on light (anti)(hyper)nuclei production at the LHC - Pinto Chiara (EPJ Web of Conferences)
For many years, significant efforts at the LHC have been put towards the measurements of the production of (anti)(hyper)nuclei in high-energy hadronic collisions. The ALICE experiment has contributed with measurements in pp, p–Pb, Xe–Xe, and Pb–Pb collisions, at various center-of-mass energies. Recently, also the LHCb experiment has measured the production of nuclei in both collider and fixed-target modes. The highlights of recent experimental measurements are discussed in the context of the production models used to describe the hadronization mechanism.